La plataforma padlet y su influencia en el rendimiento académico en la Unidad Educativa Guillermo Baquerizo Jiménez, Babahoyo. 2020 - 2021 - Burgos Ruela, María (2021)
The objective of this research was to determine the way in which the Padlet platform influences academic performance in second-year students of the Guillermo Baquerizo Jiménez Educational Unit, Babahoyo. 2020 - 2021. Likewise, it was sought to establish whether the Padlet platform influences significantly in student academic performance. For such purposes this work was developed under a causal descriptive investigation with a mixed approach and a non-experimental design. The population consisted of 70 students enrolled in the second high school, no sample is taken because it is a relatively small population, the technique to collect the data was surveys, questionnaires. However, the conclusions of this study showed: 1 that the Padlet Platform variable is significantly related to the Academic Performance variable.